A Arqueologia Aérea: Métodos e Técnicas para a Observação de Dolmens. O Caso de Mora e Arraiolos. - Câmara, Ariele (2017)
Aerial archaeology allows the observer to observe the world through space and understand the landscape to be natural or anthropic. Based on the understanding of aerial archaeology and the concept of photo interpretation, it is shown here how the dolmens present themselves in the vertical images, to understand how these places are inserted in the natural environment, taking as a case study the existing monuments in the areas of Mora and Arraiolos - Portugal. Thus, through the images made available through software such as Google Earth and BING, the monuments of these two regions were visualised to show their location and how they are perceived through this exploration method.